A COMPARATIVE ANALYSIS OF SUBCLINICAL HYPOTHYROIDISM IN INDIVIDUALS WITH METABOLIC SYNDROME VERSUS THOSE WITHOUT METABOLIC SYNDROME: A CROSS-SECTIONAL STUDY. - Adnan Imam; Prashant Dharepgol (Student's Journal of Health Research, 2023)
Aim: The objective is to compare the thyroid status of people with metabolic syndrome (MetS) to that of healthy controls.  Methods: This cross-sectional study was conducted in the general medicine department of a tertiary care hospital in India for a duration from February 2021 to March 2022. The study had a total sample size of 50, which consisted of 25 matched cases with metabolic syndrome and 25 controls. Chemiluminescence2 hormone analyzer, the chemiluminescence test was used to analyze T3, T4, and TSH. Through internal and external quality initiatives, the biochemical assays were regularly observed.  Results: Of the study population, 55% of the controls were male and 45% were female, while there was a little female predominance of 57% female and 41% male among the cases. The study population's mean age was 47.36 ± 11.20 for controls and 50.21± 9.86 for cases. There was a significant difference (p-value < 0.0001) among the patients and controls in every Met S component. TSH revealed a significant difference, with the mean TSH in the control being 3.01± 0.32 while in the cases being 8.32 ± 3.02. The most common type of thyroid dysfunction in people with Met S is subclinical hypothyroidism (SCH), which is seen in 23% of cases. Overt hypothyroidism is found in 5% of cases, whereas there are no occurrences of overt hyperthyroidism.  Conclusion: A high frequency of TD was seen in individuals with metabolic syndrome, suggesting a potential interaction between metabolic syndrome and thyroid function. The most common TD among Indian MetS patients was hypothyroidism. Recommendation: Since metabolic syndrome (MetS) patients have a high prevalence of thyroid dysfunction (TD), healthcare providers should consider routine thyroid function assessments, especially for subclinical hypothyroidism, the most common thyroid disorder in this population. Additional research is needed to understand how MetS affects thyroid function.